Association of Park Size, Distance, and Features With Physical Activity in Neighborhood Parks - Kaczynski, Andrew T. (American Public Health Association, 2008)
Objectives. We studied whether park size, number of features in the park, and distance to a park from participants’ homes were related to a park being used for physical activity. Methods. We collected observational data on 28 specific features from 33 parks. Adult residents in surrounding areas (n=380) completed 7-day physical activity logs that included the location of their activities. We used logistic regression to examine the relative importance of park size, features, and distance to participants’ homes in predicting whether a park was used for physical activity, with control for perceived neighborhood safety and aesthetics. Results. Parks with more features were more likely to be used for physical activity; size and distance were not significant predictors. Park facilities were more important than were park amenities. Of the park facilities, trails had the strongest relationship with park use for physical activity. Conclusions. Specific park features may have significant implications for park-based physical activity. Future research should explore these factors in diverse neighborhoods and diverse parks among both younger and older populations.